Impact of Lavender Aromatherapy Massage on Infant Sleep Quality in 2024 - Lormita Purba (International Journal of Health and Social Behavior, 2024)
This study investigated the effect of lavender aromatherapy massage on the quality of infant sleep in 2024. A randomized controlled trial was conducted with 60 healthy infants aged 3 to 12 months, who were divided into two groups: one group received a 10-minute lavender oil massage before bedtime, while the control group received a similar massage without lavender oil. Sleep quality was measured over two weeks using parental reports and actigraphy. The results showed that the lavender aromatherapy massage group had significantly longer sleep durations, fewer night awakenings, and improved overall sleep quality compared to the control group. The study concluded that lavender aromatherapy massage is a safe and effective method to enhance sleep quality in infants, making it a valuable addition to bedtime routine.